Characteristics of myocardial work during exercise stress echocardiography in healthy adults - Huang, Liwei; Ye, Luwei; Zhang, Hongmei; Zhang, Qingfeng; Ding, Geqi; Li, Chunmei; Deng, Yan; Yin, Lixue; Wang, Yi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundNon-invasive myocardial work (MW) is a more precise parameter for evaluating left ventricular (LV) systolic function. However, studies examining sex-based differences in MW during exercise stress echocardiography (SE) in healthy individuals are scarce. Previous research has shown that global work efficiency (GWE) decreases following exercise.ObjectivesTo characterize sex-based differences in MW during exercise SE in healthy adults and to explore the factors influencing the decline in GWE post-exercise.MethodsThe study enrolled 200 healthy adults, all of whom underwent echocardiographic assessments both at rest and immediately after completing a symptom-limited treadmill stress test. We measured LV volume, ejection fraction (EF), force, peak positive strain (PPS), global work index (GWI), global constructive work (GCW), global wasted work (GWW), and GWE at rest and post-exercise.ResultsGWI, GCW, and GWW increased, while GWE decreased after exercise. There were no significant differences in any of the global MW parameters between sexes at rest (all p > 0.05). The change in △GWE was greater in women (p < 0.05), but no significant differences were found in other MW reserve parameters between sexes. The multivariable linear regression analysis revealed that GWW was independently associated with PPS (β = 0.842, p < 0.0001) and force (β = 0.306, p = 0.023). Furthermore, the multivariable linear regression analysis showed that GWE was independently associated with PPS (β = −0.395, p = 0.018) and EF (β = −0.236, p < 0.001).ConclusionSex had a minimal effect on MW-based LV systolic function in healthy adults. GWE decreased post-exercise, and both PPS and force were independently associated with GWW. These findings suggest that higher contractility is achieved at the cost of increased wasted work, which subsequently leads to a decrease in mechanical efficiency.